The Role of Immigration in Preventing the Crime of Trafficking in Persons (TTPO) - Laoly, Grace Angelina Kristin; Simamora, Janpatar (Manunggal Halim Jaya, 2025)
This study discusses the role of immigration in efforts to prevent the Crime of Human Trafficking (TPPO) in Indonesia, considering the increasingly complex human trafficking networks involving cross-border movement. The background of this study is based on the high number of TPPO cases in Indonesia, which requires comprehensive action from various parties, including immigration as the frontline in border control. This study uses a normative legal research method, with a qualitative approach through literature studies, laws and regulations, and other secondary data to understand the role of immigration in preventing TPPO. The results of the study indicate that the Directorate General of Immigration plays an important role in identifying and preventing human trafficking practices through several main steps: border control, travel document checks, TPPO mode detection, and international cooperation. In addition, immigration is also involved in educating the public and prospective migrant workers about the dangers of TPPO and providing protection for victims who are found. The conclusion of this study emphasizes that although the role of immigration is very significant, efforts to prevent TPPO require cross-institutional collaboration and capacity building in various lines to achieve higher effectiveness in overcoming human trafficking.